2002
DOI: 10.1002/ajim.10121
|View full text |Cite
|
Sign up to set email alerts
|

Hematological changes among Chinese workers with a broad range of benzene exposures

Abstract: The depressions in RBC, WBC, and neutrophils observed in this study are not only exposure dependent, but also significantly different in the lowest exposed group (at or below 0.25 ppm) compared with unexposed subjects. The results of the present study appear to suggest that lymphocytes may not be more sensitive to chronic benzene exposure than neutrophils.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
89
1
7

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 117 publications
(110 citation statements)
references
References 12 publications
13
89
1
7
Order By: Relevance
“…24 This study found evidence of low-level benzene concentrations having an effect on peripheral blood WBCs. This finding is consistent with other studies conducted in China among shoemakers, [25][26][27] but contrary to a study in the Netherlands. 28 It is possible that the doserelationship between low benzene exposure in exposed workers and the life exposure in internal controls was modified by other factors in the Netherlands study, such as small numbers, worker protection, and life factors (e.g.…”
Section: Discussionsupporting
confidence: 88%
“…24 This study found evidence of low-level benzene concentrations having an effect on peripheral blood WBCs. This finding is consistent with other studies conducted in China among shoemakers, [25][26][27] but contrary to a study in the Netherlands. 28 It is possible that the doserelationship between low benzene exposure in exposed workers and the life exposure in internal controls was modified by other factors in the Netherlands study, such as small numbers, worker protection, and life factors (e.g.…”
Section: Discussionsupporting
confidence: 88%
“…Although they are also secreted by other cells, platelets remain the most abundant and the most rapidly available source for these CXC-chemokines (17,18). It is well established that benzene lowers peripheral platelet counts (7)(8)(9), raising the possibility that our finding could be explained entirely or in part by a decrease in platelet counts among the exposed subjects. However, we determined that the absolute platelet count did not significantly impact on the difference in expression of PF4 and CTAP-III between benzene exposed and unexposed subjects by using linear regression on the natural logarithm of each protein adjusted and unadjusted for platelet count (Table 3).…”
Section: Confirmation Of Protein Biomarkersmentioning
confidence: 78%
“…Benzene is an established cause of acute myeloid leukemia and myelodysplastic syndromes and may play a role in lymphocytic leukemias and non-Hodgkin lymphoma in humans (1)(2)(3)(4)(5)(6). Additionally, changes in blood and bone marrow consistent with hematotoxicity are recognized in humans and experimental animals (7)(8)(9). Benzene also produces immunosuppressive effects in exposed animals and humans and has been shown to increase susceptibility to tuberculosis and other infectious agents (10,11).…”
mentioning
confidence: 99%
“…O benzeno absorvido é excretado pela via metabólica do ácido mucônico e do fenol, seguida de excreção urinária dos conjugados (sulfatos ou glucuronatos). Exposições humanas de benzeno no ar, em concentrações entre 0,1 e 10 ppm, resultam em perfis de metabólitos urinários com 70-85% de fenol, 5-10% de hidroquinona, 5-10% de ácido trans,trans-mucônico e de catecol e menos de 1% de ácido S-fenilmercaptúrico 6,7 .…”
unclassified